Yahoo Web Search

  1. Sort by

  1. Here's the first as an example of the layout: LHS = cosθcotθ = cosθ * cosθ/sinθ ... because cotθ = 1/tanθ = cos^2θ / sinθ = (1 - sin...

    1 Answers · Science & Mathematics · 28/01/2015

  2. http://s1169.photobucket.com/user/chibuckt/media/IMG_20140808_0001_zps3addacb7.jpg.html?filters[user]=127216769&filters[recent]=1&sort=1&o=0

    3 Answers · Science & Mathematics · 11/08/2014

  3. 9) LHS = cos ( x + y - y ) LHS = cos...LHS = sin x - ( sin y / cos y )*cos x LHS = (sin x cos y - sin y cos x ) / cos...2 x cos^2 y - sin^2 x sin^2 y ) LHS = ( sin^2 x - sin^2 x sin^2 y - sin...

    2 Answers · Science & Mathematics · 18/04/2013

  4. sin x + sin 2x = sin x + 2 sin x cos x = sin x (1 + 2 cos x) 1 + cos x + cos 2x = 1 + cos x + (2cos^2 x - 1) = cos x + 2 cos^2 x = cos x (1 + 2 cos x) ∴ (sin x + sin 2x)/(1 + cos x + cos 2x) = sin x(1 + 2 cos x)/[cos x(1 + 2 cos x)] = sin x/cos x = tan x. Note that the double-angle identities for sine and cosine were...

    3 Answers · Science & Mathematics · 25/05/2012

  5. Expand the RHS -2[sin(x/2)cos(y/2)+sin(y/2)cos(x/2)][sin(x/2)cos(y/2)-sin(y/2)cos(x/2)]=-2[sin^2(x/2cos^2(y/2)-sin^2(y/2)cos^2(x/2)] using difference of two squares change the cos^2(y/2)=1-sin^2(y/2) and cos^2(x/2)=(1-sin^2x/2) to obtain -2(sin^2(x/2)-sin^2(y/2)) convert the sin^2(x/2) and sin^2(y/2) to the double...

    1 Answers · Science & Mathematics · 20/06/2013

  6. ... LHS = sin⁴ x + cos⁴ x = ( sin² x )² + ( cos²...

    1 Answers · Science & Mathematics · 08/08/2010

  7. LHS = (1 + cos(x)) / (1 - cos(x)) = ((1 + cos(x))/cos(x)) / ((1-cos(x))/cos(x)) = (sec(x) + 1) / (sec(x) - 1) = (1 + sec(x)) / (sec(x) - 1) = RHS LHS = (sin(x) + tan(x)) / (cos(x) + 1) = (sin(x) + sin(x)/cos(x)) / (cos(x) + 1) = sin(x...

    1 Answers · Science & Mathematics · 03/06/2008

  8. a). LHS: sinx + tanx Now I multiply them to cosx/cosx meaning I multiply...cosθ)] (sinθ + cosθ) cancel out = (sinθ - cosθ)/cosθ = sinθ/cosθ - cosθ/cosθ = tanθ - 1 = LHS Proved.

    3 Answers · Science & Mathematics · 15/05/2012

  9. LHS sin^6(x) = [sin^2(x)]^3 = [1 - cos^2(x)]^3 [1 - cos^2(x)]^3 + cos^6(x) (1 - 3cos^2(x) + 3cos^4(x) - cos^6(x)) + cos^6(x) 1 - 3cos^2(x) + 3cos^4(x) RHS 1 - 3(1 - cos^2(x))cos^2(x) 1 - 3cos^2(x) + 3cos^4(x) LHS = RHS

    3 Answers · Science & Mathematics · 27/11/2012

  10. LHS=cos(2x) / 1 + sin(2x) =(cox^2x- sin^2x) /(cox^2x+sin^2x +2sinx.cosx) =(cosx +sinx).(cosx...x) ..............=(tanpi/4 - tanx)/(1+tanpi/4tanx) ..............=(1-tanx)/(1+tanx) ..............=LHS at "A"

    2 Answers · Science & Mathematics · 22/11/2009

  1. Ad
    related to LHS
  1. Try asking your question on Yahoo Answers